A new species of genus Dodona Hewitson, 1861 from western Yunnan, China (Lepidoptera: Riodinidae) - Hu, Shao-Ji; Jiang, Zhuo-Heng; Zhang, Hui-Hong; Duan, Kuang; Zhang, Xin (Zootaxa, 2026)
A new species of the riodinid genus Dodona Hewitson, 1861, Dodona yehuii Hu & Jiang sp. nov., is described from montane areas in northwestern Yunnan, China. The new species is placed within the D. eugenes species group based on the combination of morphological and molecular evidence. The new species is sister to D. formosana Matsumura, 1919, endemic to Taiwan Island. The Kimura 2-parameter genetic distances between D. yehuii sp. nov. and other congeneric taxa in the D. eugenes group exceeds 3%, supporting it as a distinct species. Descriptions of the adults and genitalia of both sexes are provided, alongside a discussion of its diagnostic characters, habitat, and behaviour. An updated checklist of the genus Dodona in Yunnan is also presented.